Nature-derived Ultrahigh-performance Aromatic Bioplastics - Nag, Aniruddha; Kaneko, Tatsuo (Vietnam Journal of Science and Technology, 2022)
Biomass, a renewable carbon source which can be processed using biorefinery system as an alternative of the conventional petroleum-based refineries. Aromatic precursor molecule synthesis involves chemical synthesis of fossil-fuel-based starting materials, such as benzene and xylene. These energy-intensive processes are usually producing many byproducts along with the desired molecule. If aromatic molecules can be extracted from natural resources involving minimum chemical conversions, that can be advantageous. Most of the reported approaches are expensive in nature and the outcomes with lower yield. Microbial fermentation of the lignocellulosic derivatives are ideal to establish sustainable society. In this chapter, we will focus on the aromatic building block preparations starting from nonedible feedstock such as kraft pulp. Aromatic aminobenzoic acid (3-amino-4-hydroxybenzoic acid) preparation from renewable resources and its use in various polymer preparations, such as polyaniline, polyester, and polybenzazole will be discussed here.